COASTAL RESOURCES CO-MANAGEMENT THROUGH LOCAL COMMUNITIY LIVELIHOOD IMPROVEMENT IN CU LAO CHAM ISLANDS, QUANG NAM - Trinh, Chu Manh (Vietnam Journal of Marine Science and Technology, 2008)
Coastal  areas  are  facing  with  environmental  and  resources sustainable development.  One of them  is  how  livelihood improvement of the community who -living inside or around the coastal rosource  areas. Especially, in  locality where  most of local people life depending strongly upon coastal environment and resources.The  sharing rights - benefits between government and community (co-managmement) in  reasonable utilisation and protection of coastal resources is  consider as  an  useful tool for local level.  Among, include aspects relating to local livelihood improvement.Based  on  studied  results  of livelihood  improvement  in high-quality  fish  sauce development  in  Cu  Lao  Cham  islands, Quang Nam  province,  comanagement application  in local level is primarily achieved in theory and also in practice.The  paper  presents  the  concepts  of  comanagement,  livelihood and  sustainable livelihood,  as  well  as  presents  local  livelihood proceed  in  case  of high-quality fish  sauce livelihood  for  Cu  Lao Cham  community  which  contribute  to  the  coastal  environment protection and resources reasonable utilisation in the marine protected area.